Reversible lithium electroplating for high-energy rechargeable batteries - Ding, Ning (2023)
Electrification is seen as one of the key strategies to mitigate the growing energy demands in areas like transportation. With electrification, a better and safer energy storage system becomes a pressing need. Therefore, Li-based batteries are gaining popularity due to their high theoretical capacities. However, the use of Li-based batteries had been fraught with safety concerns. Specifically, Li dendrite formation during Li-plating can cause shorting in cells and thermal runaway. To that end, much effort has been put into mitigating the growth of these dendrites. To tackle this issue, the mechanisms involved in the formation of different morphologies of the plated Li is highlighted, as it determines, to a large extent, the mechanical properties of the plated Li. In turn, the mechanical properties of the plated Li will affect the cyclability and the overall safety of the battery. However, the yield strength of most materials used in separators and solid electrolytes are usually not high enough to prevent penetration by Li dendrites. Hence, various strategies to control the growth and morphology of Li deposits that can form dendrites, has been highlighted here as these strategies are key research directions for the advancement of high energy density Li-based batteries.